Efektivitas Manajemen Risiko Perusahaan Terhadap Kinerja Keuangan dan Nilai Perusahaan : Peran Moderasi Tanggung Jawab Lingkungan Perusahaan (TJL) - Arinda Herliana; Rita Wijayanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the effect or effectiveness of Corporate Risk Management on the financial performance and value of the company : Corporate Environmental Responsibility (CSR). The population of this study is manufacturing companies in Indonesia. This research sample uses data collection this research uses secondary data information obtained from 162 environmentally sensitive companies in Indonesia that publish financial reports and sustainability reports for the period 2022 and 2023. The results of this study showed that ERM / risk management has a positive influence on the value of the company, the company's Environmental Responsibility has a positive influence on the value of the company, environmental responsibility managed to moderate the positive influence of risk management on the value of the company. This study has a contribution in identifying the influence of risk management as an independent variable on the financial performance and value of the company which is assisted by the variable moderation of corporate environmental responsibility (TJL).